Género, poder y literatura en la España contemporánea - Alonso Valero, Encarna (Acta Hispanica, 2010)
This paper analyzes the images of power and the consecration mechanisms that can be found in the pathways of several political women in the first third of the 20th century in Spain. To that end, this work considers concepts like the idea of merit and the idea of exceptions creation, among others. The construction of national feminine myths is also analyzed, giving a detailed overview about the utilization of music and literature as effective resources to conform those miths.